Sistem Aplikasi Berbasis Web SMK Solusi Efisien untuk Monitoring Kehadiran Siswa SMK Menggunakan Model Prototype - Adinda Sri Wahyuni; All Iqbar Arifin; Nurdiasih Nurdiasih; Wasis Haryono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The rapid development of information technology demands the creation of innovative and efficient solutions across various fields of life. In this study, a web-based system was developed with the aim of creating a student attendance and income reporting system that can be accessed in real time. The development methodology used in this system is the prototype model, consisting of stages such as requirements analysis, system design, implementation, and testing. The testing results show that the developed system significantly improves accessibility. Therefore, this research is expected to contribute positively to the development of information technology and its application in real-life situations.